2019
DOI: 10.1371/journal.pgen.1008315
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ARL2BP, a protein required for ciliary microtubule structure, cause syndromic male infertility in humans and mice

Abstract: Cilia are evolutionarily conserved hair-like structures with a wide spectrum of key biological roles, and their dysfunction has been linked to a growing class of genetic disorders, known collectively as ciliopathies. Many strides have been made towards deciphering the molecular causes for these diseases, which have in turn expanded the understanding of cilia and their functional roles. One recently-identified ciliary gene is ARL2BP , encoding the ADP-Ribosylation Factor Like 2 Binding Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Patients were ascertained at the Instituto de Oftalmologia Dr. Gama Pinto in Lisbon, Portugal, and informed consent was obtained from all family members included in this study. Clinical and ophthalmological assessment was performed as previously described (Moye et al, 2019). Audiological examinations were provided to us by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were ascertained at the Instituto de Oftalmologia Dr. Gama Pinto in Lisbon, Portugal, and informed consent was obtained from all family members included in this study. Clinical and ophthalmological assessment was performed as previously described (Moye et al, 2019). Audiological examinations were provided to us by the patients.…”
Section: Methodsmentioning
confidence: 99%
“…The same was true for the two other studies, where the presence of false-positive heterozygous genotypes was combined with the relatively short size of ROHs and/or the presence of a limited number of identifiable genotypes. In addition, AutoMap enabled the detection of new variants in a number of genes that were already associated with Mendelian conditions [35][36][37] . In conclusion, AutoMap is a reliable tool that can predict ROHs with high specificity and sensitivity, in less than a minute, even from VCF files derived from noisy exome sequencing data.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent GO analysis showed that these genes were mainly enriched in BP category including spermatogenesis, multicellular organism development, cell differentiation, spermatid development, and sperm motility, as well as in CC category including motile cilium, microtubule, acrosomal vesicle and nucleus. These are also the hotspots of research on male infertility from the transcriptome level in recent years ( Moye et al, 2019 ; Wang et al, 2019b ; Yuan et al, 2019 ; Goto, et al, 2020 ). KEGG pathway analysis results indicated that the pathways that DEGs might affect sperm development were mainly enriched in glycolysis/gluconeogenesis, protein processing in endoplasmic reticulum, carbon metabolism and cell cycle.…”
Section: Discussionmentioning
confidence: 99%